New security dimensions in the Asia Pacific - Desker, Barry (2009)
The paper highlights four key aspects of the new security dimensions in Asia-Pacific. First, the US role in the Asia-Pacific is changing. While the US will remain a major player in the Asia-Pacific, it will no longer be the 800 pound gorilla in the region and will have to handle the emerging ambitions of a rising China, which could play the role of a regional challenger. Secondly, the states of the region, includign the members of ASEAN and Australia, will have to deal with the rise of China. Thirdly, the rise of China is being accompanied by growing Sino-Japanese tensions which need to be managed, the parallel rise of India (which could pose a strategic challenge to China) and the articulation of Chinese norms and values embodied in the Beijing Consensus which is challenging the Washington Consensus of Western norms and values, which has shaped international institutions since the end of the Cold War. Fourthly, Asia's security architecture is undergoing profound changes and a closer examination of the new overlapping regional multilateral institutions in the Asia-Pacific is warranted. The paper concludes by discussing the implications of Australia, before suggesting possible implications of these developments for policy-oriented research centres of international affairs.